Some Viable Strategies for Classroom Assessment — A Field Experience - K, Vijayan. (JOURNAL OF INDIAN EDUCATION, 2014)
National Curriculum Framework (NCF) 2005 and its position paper on ‘Examination Reform’ have recommended the implementation of Continuous and Comprehensive Evaluation (CCE) at all levels of school education for maintaining quality. RTE Act 2009 also stressed this aspect through its section 24(1)(d) and section 29(2)(h). Many state boards and national board like CBSE have already initiated the process of assessing students learning through different strategies as a part of Formative Assessment (FA) and Summative Assessment (SA). The present article elaborates some of the assessment strategies practiced by the author as a part of classroom activity during a three-month field work at Central School for Tibetans, Bylakkupe, Karnataka. The article illustrates experience of administering peer assessment, self assessment and quiz as classroom assessment strategies in an integrated way. These strategies can embed with learning activities in a learning environment which offers collaboration and cooperation. Peer assessment and self assessment are two effective strategies for encouraging students to involve in the learning process for improving their performance. Through the critical review of the work done by themselves, the students will be able to recognise the strong as well as weak areas of their learning during the activity. Here they are assessing critically both what and how they are learning. Even though most quiz programmes are summative in nature, one can innovate it by changing the procedure as an effective formative assessment strategy. This is also known as formative use of summative assessment. Here quiz has been used in the form of a group game to assess student’s performance. It will help the teacher to assess the ability of each student to frame questions, derive the answers in group setting, ability to ask and respond to the questions. The whole process will help the teacher to get a clear idea about the level of performance of individual students in a particular topic. The procedure followed by the teacher and the feedback received from the students about these different strategies are elaborated in this article.